Pemanfaatan Software Netsupport School Terhadap Peningkatan Hasil Belajar Siswa Pada Mata Pelajaran Desain Grafis Percetakan Kelas XI Multimedia Smk Negeri 2 Bone - Darman; Syarifnur; A. Suharman; Syarifah (Berugak Baca, 2024)
This research is a classroom action research aimed at improving student learning outcomes in the Graphic Design Printing subject for Class XI Multimedia students at SMK Negeri 2 Bone by utilizing Netsupport School Software. The subjects of the study consisted of 23 students from Class XI Multimedia. Data collection techniques used were tests, observation sheets, and documentation. The collected data were analyzed descriptively. The success indicators of the action were marked by 75% of the students participating in the learning process achieving a score of ≥ 75 on the post-test of cycle II. The research results showed that the percentage of students achieving a score of ≥ 75 in cycle I was 43.48%, which increased by 34.82% to 78.3% in cycle II. The conclusion of this study is that the utilization of Netsupport School Software can improve the learning outcomes of Class XI Multimedia students at SMK Negeri 2 Bone